Assessment of heavy metal contamination in soil around Piyungan Landfill, Yogyakarta, Indonesia - Mufid Muyassar; Wawan Budianta (Journal of Applied Geology, 2021)
One of the negative impacts of the landfill as solid waste disposal is soil contamination by heavy metals. This study assessed heavy metals impact, especially Pb, Cu, Zn, and Cd, in the soil in Piyungan landfill, Bantul, Yogyakarta, Indonesia. The assessment was conducted by analyzing 15 soil samples from 25 cm depth in the study area, which was divided into three-zone. The study results showed that generally, the highest content of metals was found in zone II, which is located near or directly situated in a landfill site. The pollution index (PI) calculated showed in order Cd>Cu>Pb>Zn. The result also indicates that Cd has the highest pollution index and even the highest risk compared to Pb, Cu, and Zn. The eco-risk index (RI) calculation showed that the value was 29 to 70 demonstrating a low class. The result also indicates that the accumulation of heavy metals investigated in this study was normal, and that the ecological risk was relatively low.